Strategy, profits & ethics: Beyond the work of miles - Galbreath, Jeremy (Curtin University of Technology, 2006)
A prominent feature of the management ? and increasingly marketing ? literature is offering normative prescriptions to corporate strategists for maximizing profits. However, with few exceptions, the ethicality of various profit making strategies has not been analysed or debated. Building upon previously developed ethical criteria, this paper assesses five profit making strategies widely discussed in the literature. Our results reveal that strategy approaches for making profits based on industrial organization (IO) economics seem to largely fail the ethical criteria while Austrian, core competency, dynamic capabilities and market orientation approaches seem to fair much better. For scholars involved in the teaching of strategy, this study clearly demonstrates that ethics cannot be ignored in the classroom. For corporate strategists, examining their approach to making profits should come under the careful scrutiny of an ethical lens, such as one described in this paper.